Heparin Resistance, Measured by the Plasma Heparin Thrombin Time, in Patients on Long-term Anticoagulant Therapy with Phenylindanedione Following Coronary Occlusion - Holger-Madsen, T; Schioler, M (Thrombosis and Haemostasis, 1960)
Of 74 patients with a history of coronary occlusion 42 received anticoagulant (phenylindanedione) therapy, while 32 were untreated. Both groups were investigated in a comparative study of prothrombin determination, heparin tolerance test, and plasma heparin thrombin time. By the latter method the clotting time with thrombin is determined on heparinized, platelet-poor citrated plasma. In several patients on anticoagulant therapy whose prothrombin-proconvertin level was well adjusted and whose heparin clotting time, as measured by the heparin tolerance test, was definitely prolonged in relation to normal, an increased heparin resistance might still be demonstrated in the form of a distinct shortening of the heparin thrombin time. In the majority of the treated patients the anticoagulant therapy had entailed a prolongation of the heparin clotting time as measured by the heparin tolerance test. As measured by the heparin thrombin time, however, the treatment was found to have had no influence on the heparin resistance, there being no difference between the frequency of shortened heparin thrombin time in the treated and in the untreated group.